AN ANALYSIS OF STUDENTS’ READING SKILLS IN COMPREHENDING RECOUNT TEXTAT TENTH GRADE OF SMA N 3 BUKITTINGGI - Diffa Amanda; Eliza Eliza; Merry Prima Dewi; Loli Safitri (Adisam Publisher, 2025)
One of the most important skills in learning English is reading. For comprehending or getting the information from the texts wich will be read needs reading skills. In this research the researcher formulates the question to be “How is the students’ reading skills in comprehending recount text at tenth grade of SMA N 3 BUKITTINGGI?”.The researcher used a descriptive quantitative.The populationin this research is tenth grade students’ of SMA N 3 BUKITTINGGI and in the SMA N 3 BUKITTINGGI has 9 classes for the ten grade with total 324 students’. In this research, the researcher choose one class to be a sample. Instrument the researcher used is test, the researcher used test to analyze students’ reading skills’ in comprehending recount text. The result of analysis there are four categorys obtained from the answer sheets test of recount text at the tenth grade of SMA N 3 BUKITTINGGI. There are 20 students’ obtained excellent category, there are 5 student’s obtained good category, there are 7 students’ obtained fair category and there are 2 students’ obtained poor category. Overall the students’ reading skills at tenth grade is good but, there are two reading skills’ identifying the topic and skimming where the saveral students’ still having difficulty to the determining.